Technology of cryosublimation fractionation in production of biologically active curative-table waters - Osetsky, Oleksandr; Sevastianov, Stanislav; Potapov, Volodymyr; Bilyi, Dmytro; Piliugina, Inna (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):311